Communications and Multimedia Security 13th IFIP TC 6/TC 11 International Conference, CMS 2012, Canterbury, UK, September 3-5, 2012. Proceedings - Decker, Bart.; Chadwick, David W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 13th IFIP TC 6/TC 11 International Conference on Communications and Multimedia Security, CMS 2012, held in Canterbury, UK, in September 2012. The 6 revised full papers presented together with 8 short papers, 8 extended abstracts describing the posters that were discussed at the conference, and 2 keynote talks were carefully reviewed and selected from 43 submissions. The papers are organized in topical sections on image and handwriting analysis, authentication and performance, biometrics, forensics and watermarking, and communications security.
Image and Handwriting Analysis -- Authentication and Performance -- Biometrics, Forensics and Watermarking -- Communications Security.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Biometrics; Information Systems; Computer Science; Systems and Data Security; Biometrics; e-Commerce/e-business.; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems